2019
DOI: 10.1123/japa.2017-0297
|View full text |Cite
|
Sign up to set email alerts
|

Age Does Not Attenuate Maximal Velocity Adaptations in the Ipsilateral and Contralateral Limbs During Unilateral Resistance Training

Abstract: This study examined the effects of unilateral resistance training (RT) on maximal velocity parameters in the ipsilateral and contralateral legs in young and older males. Young (n = 22; age = 21.55 ± 2.23 years) and older (n = 20; age = 65.10 ± 9.65 years) males were assigned to training or control groups. Unilateral isokinetic RT of the knee extensors was performed for 4 weeks. Peak velocity and acceleration were identified during a dynamic maximal voluntary contraction before (PRE), at Week 2 (MID), and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In this study, we found that walking had a positive effect on emotional health, which was consistent with previous research [ 24 , 25 , 26 , 27 , 28 , 29 ]. A potential explanation for this could be that when walking, individuals may come in contact with nature, which soothes the body and mind.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that walking had a positive effect on emotional health, which was consistent with previous research [ 24 , 25 , 26 , 27 , 28 , 29 ]. A potential explanation for this could be that when walking, individuals may come in contact with nature, which soothes the body and mind.…”
Section: Discussionsupporting
confidence: 93%
“…Kekäläinen et al [ 25 ] demonstrated that walking was positively associated with participants’ mental, social, and subjective health. Moreover, research found that walking-based exercise training alleviated anxiety and depression in adults, and moderate and intense walking exercise promoted lower blood pressure and improved mental health by reducing negative emotions [ 26 , 27 ]. In addition, in individuals who generally prefer more casual forms of exercise, such as walking, increasing walking during leisure time can reduce the generation of negative emotions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-education has been extensively investigated since before the 20 th century (Scripture 1894). It involves the performance improvement of the untrained limb after a period of unilateral practice (i.e., strength, acceleration, skill, endurance) (Hortobagyi 2005;Carroll et al 2006;Farthing et al 2007;Farthing 2009;Hester et al 2018). Substantial evidence for cross-education has been demonstrated in adults for contralateral homologous muscles such as the quadriceps (Kannus et al 1992;Hortobagyi et al 1997;Evetovich et al 2001;Goodwill et al 2012;Latella et al 2012), elbow flexors (EF) (Ebersole et al 2002;Munn et al 2005;Adamson et al 2008), and hand grip muscles (Shields et al 1999;Manca et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The association between PA and the risk of falling in elderly was recently evaluated by systematic review and meta-analysis. These analyses came out with the conclusion that the risk of being a recurrent faller (two or more self-reported falls over the follow-up period of 12–36 months) was 39% higher in older adults with the lowest levels of PA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%